Tissue communication in regenerative inflammatory signaling: lessons from the fly gut - Kux, Kristina; Pitsouli, Chrysoula (Frontiers in Cellular and Infection Microbiology, 2014)
The intestine, as a barrier epithelium, serves in the first line of defence against invading pathogens and damaging agents that enter the body via food ingestion. Maintenance of intestinal homeostasis is therefore key to organismal health. To maintain homeostasis, intestinal stem cells (ISCs) continuously replace lost or damaged intestinal epithelial cells in organisms ranging from Drosophila to humans. Interestingly, intestinal damage upon ingestion of chemicals or pathogenic bacteria leads to an inflammatory response in the Drosophila intestine, which promotes regeneration and predisposes to tumorigenesis. This regenerative inflammatory signalling culminates in proliferation and differentiation of ISCs that replenish the damaged intestinal cells and is regulated by the interplay of conserved cell-cell communication pathways, such as the JNK, JAK/STAT, Wnt/Wingless, Notch, InR, PVR, EGFR and Hippo. These pathways are induced by signals emanating not only from the damaged intestinal epithelial cells, but also from neighboring tissues associated with the intestinal epithelium, such as the muscles and the trachea, or distant tissues, such as the wounded epidermis and the brain. Here we review tissue communication during homeostasis and regenerative inflammatory signalling in Drosophila focusing on the signals that emanate from non-intestinal epithelial tissues to ensure intestinal integrity.